2019
DOI: 10.1002/alr.22443
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of steroid‐eluting stents in management of chronic rhinosinusitis after endoscopic sinus surgery: updated meta‐analysis

Abstract: Background:Recently, there has been mounting evidence suggesting the efficacy of steroid-eluting stents (SES) for management of chronic rhinosinusitis a er endoscopic sinus surgery (ESS). This meta-analysis serves to evaluate the efficacy of SES in improving postoperative outcomes a er ESS. Methods:A systematic literature search was performed of PubMed for articles published between 1985 and 2018. The outcome variables were reported at, on average, 30 days postintervention.Results: Seven of the 76 published st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…One such case report describes a hypersensitivity reaction occurring in a patient with a retained stent, 4 but otherwise there have been no device-related reports of fungal colonization or infection in any randomized controlled clinical trials or case reports. 2,3,5,6 One animal study evaluating effects of Propel™ stents in a rabbit model showed superficial fungal colonization in 6 of 30 rabbit sinuses implanted with steroid-impregnated stents, but also in 3 of the 20 sinuses with control stents, with no statistical difference between groups. The fungal hyphae and spores were found on the stent and within the lumen of the sinus, but there was no evidence of invasion into the tissue or associated inflammatory changes in either the test or control group.…”
Section: Introductionmentioning
confidence: 99%
“…One such case report describes a hypersensitivity reaction occurring in a patient with a retained stent, 4 but otherwise there have been no device-related reports of fungal colonization or infection in any randomized controlled clinical trials or case reports. 2,3,5,6 One animal study evaluating effects of Propel™ stents in a rabbit model showed superficial fungal colonization in 6 of 30 rabbit sinuses implanted with steroid-impregnated stents, but also in 3 of the 20 sinuses with control stents, with no statistical difference between groups. The fungal hyphae and spores were found on the stent and within the lumen of the sinus, but there was no evidence of invasion into the tissue or associated inflammatory changes in either the test or control group.…”
Section: Introductionmentioning
confidence: 99%
“…The results still revealed an identical trend for studies using non‐steroid‐releasing implants as a placebo group. Previous studies that have focused on the efficacy of steroid‐eluting implants have also demonstrated trends of favoring steroid‐eluting implants compared with the control group 31–34 . It also consumed more health care expenditure than diseases such as peptic ulcer disease, acute asthma, and hay fever 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that have focused on the efficacy of steroid-eluting implants have also demonstrated trends of favoring steroid-eluting implants compared with the control group. [31][32][33][34] It also consumed more health care expenditure than diseases such as peptic ulcer disease, acute asthma, and hay fever. 1 Postoperative management remains a critical part of chronic rhinosinusitis treatment.…”
Section: F I G U R E 4 Forest Plot Of Further Interventions Ci Confid...mentioning
confidence: 99%
“…Steroid-eluting sinus implants ( Figure 1 G) have been introduced as a new method to optimize surgical outcomes and to treat recurrent nasal polyposis after ESS by delivering locally sustained-release corticosteroids directly to inflammatory sinus tissues [ 122 ]. This can create an effective sinus drug delivery system, local use of corticosteroids to solve the problem of inflammation [ 123 ]. Currently used FDA-approved steroid-eluting sinus implants are Propel family products (Propel ® , Propel Mini ® , Propel Contour ® ) and SINUVA™.…”
Section: Methods Of Nasal Drug Deliverymentioning
confidence: 99%